Reduction of noise during milling operations. (August 2017) - Rech, J.; Dumont, F.; Le Bot, A.; Arrazola, P.J.
Abstract: With the increase in performance of machining operations, noise levels have become an occupational health and safety problems. Identification of the main sources of noise emission when milling an aluminium component was analyzed. A machining centre, equipped with microphones, was installed in an anechoic chamber. Testing demonstrated that the part's stiffness is the most critical parameter. Cutting speed, feed and axial depth of cut tend to increase sound pressure level by increasing the impact energy, whereas radial depth of cut is not a sensitive parameter. Moreover the diameter of mills, as well as their unbalance, should be limited.